Determinação de espécies de arsênio por LC-ICP-MS - Duarte, Fábio Andrei (2006)
The development of a method for As speciation in aqueous by-product of pyrolysis process of foliate bituminous is described in the present work. Arsenic species are separated by liquid chromatography (LC) coupled to inductively coupled plasma mass spectrometry (ICP-MS). An anion exchange column was used to separated the As species. The analyzed liquid samples were centrifuged at 10000 rpm for 10 min, the supernatant filtered through a 0.45 mm pore size filter and then kept at 4 ºC until analysis. Before being inject in the chromatograph, the supernatant was filtered once more through a 0.2 mm pore size filter coupled to the syringe. In order to avoid memory effects, the supernatant was ten-fold diluted before filtration in the syringe. The separation column was of anion exchange type Dionex IonPac® AS14 (250mm x 4mm i.d., 9 mm particle size). A Dionex IonPac® AG14 (50mm x 4mm i.d., 9 mm particle size) was used as guard column. Ammonium carbonate ((NH4)2CO3) solution was used as mobile phase, according to the following program: 10 min, 0.0015 mol l-1 (NH4)2CO3; 10 min, 0.012 mol l-1 (NH4)2CO3 and 10 min, 0.02 mol l-1 (NH4)2CO3. Calibration curves of arsenobetaine (AsB), arsenite (As(III)), dimethylarsinic acid (DMA), p-arsanilic acid (p-ASA) and arsenate (As(V)) were obtained from serial dilution of standards and subsequent mixing. The retention time increased from AsB, As(III), DMA, p-ASA to As(V). Although 13 As species were separated and detected, quantification of only 3 species (As(III), DMA and As(V)) was possible. The concentrations found were 4.5, 6.9 and 808 mg l-1 of As(III), DMA and As(V), respectively. The method was validated by recovery tests, being the recoveries within 93 and 107%. The limits of detection (LODs) of AsB, As(III), DMA, p-ASA and As(V) were, 5, 4, 19, 11, 57 ng l-1, respectively, while the relative standard deviation (RSD) was typically bellow 6%.